The political Paul : justice, democracy and kingship in a Hellenistic framework - Blumenfeld, Bruno (Journal for the study of the New Testament. Supplement series ;, 2003)
The Political Paul presents Paul as a political thinker. Many studies claiming Paul for Greek Hellenism discuss the influence upon him of various aspects of Hellenistic culture, but strangely neglect Hellenistic political philosophy with its roots in Classical antiquity. The Political Paul explores this dimension of Paul+ås thought within the general context of Hellenistic political reflection to focus on the intriguing body of literature known as the Pythagorean pseudepigrapha. These researches support the highly original argument that Christianity has foundations in Hellenistic kingship theo.